Innocent - Turow, Scott (Bk 8; Kindle County Legal Thriller., 2010)
"Innocent continues the story of Rusty Sabich and Tommy Molto who are, once again, twenty years later, pitted against each other in a riveting psychological match after the mysterious death of Rusty's wife"--Provided by publisher.